2011
DOI: 10.1080/10798587.2011.10643166
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Classifier Combination For Recognition Of Wheat Leaf Diseases

Abstract: Wheat industry is an important constituent of Northern China's overall agricultural economy. Proper disease detection using computer vision and pattern recognition has being investigated to minimize the loss, and finally achieve intelligent healthy farming. This paper proposes a new strategy of Multi-Classifier System based on SVM (support vector machine) for pattern recognition of wheat leaf diseases for higher recognition accuracy. Diseased leaf samples with Powdery Mildew, Rust Puccinia Triticina, Leaf Blig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(19 citation statements)
references
References 17 publications
(25 reference statements)
0
18
0
Order By: Relevance
“…The system proposed in [5] presents a SVM-based Multiple Classifier System (MCS) for pattern recognition of wheat leaf diseases. Based on the infected images of various rice plants the paper [6] describes a software prototype system for rice disease detection.…”
Section: Existing Workmentioning
confidence: 99%
“…The system proposed in [5] presents a SVM-based Multiple Classifier System (MCS) for pattern recognition of wheat leaf diseases. Based on the infected images of various rice plants the paper [6] describes a software prototype system for rice disease detection.…”
Section: Existing Workmentioning
confidence: 99%
“…They reported that the max-wins-voting SVM with Gaussian radial Basis kernel recorded the best classification accuracy with 88.2%. Tian et al [64] developed a multiple classifier system (MCS) based on the support vector machine for pattern recognition of wheat leaf diseases. Three different features, namely, color, texture and shape, are used as training sets.…”
Section: Fruit Disease Recognition and Classificationmentioning
confidence: 99%
“…Tian et.al. [10] suggested a new method of Multi-Classifier System based on SVM for pattern recognition of wheat leaf diseases with high recognition accuracy. Diseased leaf samples with Powdery Mildew, Rust Puccinia Triticina, Leaf Blight, and Puccinia Striiformis were collected in the field and images were captured before a uniform black background.…”
Section: Related Workmentioning
confidence: 99%